Preferential Consolidation of Emotional Memory During Sleep: A Meta-Analysis - Lipinska, Gosia; Stuart, Beth; Thomas, Kevin G. F.; Baldwin, David S.; Bolinger, Elaina (Frontiers in Psychology, 2019)
It is uncertain whether sleep preferentially consolidates emotional over neutral material (i.e., whether differences in strength of memory for valenced material compared to neutral material are larger after a sleep-filled delay than after a comparable wake-filled delay). There is conflicting evidence within this literature. Some studies find evidence suggesting that, indeed, sleep enhances emotional memory, whereas others find no such effect. We attempted to resolve this uncertainty by conducting a meta-analysis that compared valenced to neutral material after both sleep- and wake-filled delays. Standard search strategies identified 31 studies (containing 36 separate datasets) that met our inclusion criteria. Using random effects modeling, we conducted separate analyses for datasets comparing (a) negative versus neutral material, (b) positive versus neutral material, and (c) combined negative and positive versus neutral material. We then specified several subgroup analyses to investigate potential moderators of the relationship between sleep and emotional memory consolidation. Results showed no overall effect for preferential sleep-dependent consolidation of emotional over neutral material. However, moderation analyses provided evidence for stronger effects when (a) studies used free recall rather than recognition outcome measures, and (b) delayed recall or recognition outcomes were controlled for initial learning. Those analyses also suggested that other methodological features (e.g., whether participants experience a full night of sleep and a regular daytime waking control condition rather than a nap and a night-time sleep deprivation control condition) and sample characteristics (e.g. all-male or not, young adult or not) should be carefully addressed in future research in this field. These findings suggest that sleep does enhance emotional memory, but that in the laboratory the effect is only observed under particular methodological conditions. The conditions we identify as being critical to consider are consistent with general theories guiding scientific understanding of memory consolidation during sleep.